Assessment of 2 Salmonella enterica serovar Typhimurium-based vaccines against necrotic enteritis in reducing colonization of chickens by Salmonella serovars of different serogroups - Jiang, Yanfen (Canadian Veterinary Medical Association, 2010)
This study assessed the protective efficacy of oral vaccination with 2 experimental attenuated Salmonella Typhimurium-vectored vaccines for necrotic enteritis in protecting chickens against intestinal colonization by common serovars of Salmonella belonging to the 4 major serogroups affecting chickens. Birds were vaccinated orally with 1 × 10(8) colony-forming units (CFU) of 1 of the vaccine strains χ9241 and χ9352, which express a plasmid-encoded partial recombinant hypothetical protein gene (tHP) of Clostridium perfringens, at days 1 and 7 of age, and then were challenged at 14 d of age with 10(6) CFU of Salmonella serovars Anatum, Enteritidis, Heidelberg, Kentucky, or Typhimurium (representative serovars of serogroups B, C, D, and E). Birds were necropsied at 4 wk of age, and samples were collected to determine reduction in tissue and intestinal colonization. The chickens vaccinated with χ9241-tHP showed reduced colonization by Salmonella Enteritidis (serogroup D) and by Salmonella Heidelberg and Salmonella Typhimurium (serogroup B) compared with the control birds. No reduction in colonization was observed in the chickens vaccinated with χ9352-tHP. There was an association between the efficacy of these vaccine strains in protecting against necrotic enteritis, assessed on an earlier occasion, and their efficacy in protecting against Salmonella colonization. Thus, the choice of an attenuated Salmonella Typhimurium vaccine vector for delivery of heterologous antigens to chickens should be based partly on the vaccine’s value in protecting against colonization by serovars within serogroups B and D. Such vectors would have the additional benefit of reducing colonization of important Salmonella serovars.